1970
DOI: 10.3126/nepjoph.v1i2.3683
|View full text |Cite
|
Sign up to set email alerts
|

Demographic pattern, clinical features and treatment outcome of patients with infective keratitis in the eastern region of Nepal

Abstract: Background: Corneal ulcer is one of the major causes of monocular blindness in developing countries. Objective:To determine demographic pattern, risk factors, microbiological pattern and treatment outcome of infective keratitis. Materials and methods:A retrospective analysis of hospital records of 44 patients with clinically-diagnosed infective keratitis presenting to B.P. Koirala Institute of Health Sciences in the eastern region of Nepal was carried out. Outcome measures:The parameters studied were risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

1970
1970
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
3
14
2
Order By: Relevance
“…This may be due to the climatic variations as Kathmandu is in hilly region with cold weather and the LEI in the sub-tropical low land. Similar findings were observed in the study done in eastern region of Nepal where only 20 % of cultures had fungal growth (Lavaju et al, 2009). Nepal J Ophthalmol 2012;4(7):119-127 Among the fungal positive cultures, 30.73 % cases were Fusarium spp, 10.06 % Aspergillus spp and the remaining were the mix of large number of fungal pathogens including unidentified hyaline fungi, unidentified dematiceous fungi spp.…”
Section: Discussionsupporting
confidence: 78%
“…This may be due to the climatic variations as Kathmandu is in hilly region with cold weather and the LEI in the sub-tropical low land. Similar findings were observed in the study done in eastern region of Nepal where only 20 % of cultures had fungal growth (Lavaju et al, 2009). Nepal J Ophthalmol 2012;4(7):119-127 Among the fungal positive cultures, 30.73 % cases were Fusarium spp, 10.06 % Aspergillus spp and the remaining were the mix of large number of fungal pathogens including unidentified hyaline fungi, unidentified dematiceous fungi spp.…”
Section: Discussionsupporting
confidence: 78%
“…Majority of keratitis cases were seen in the agricultural group (47.2%) similar to other studies done by Upadhyay MP et al (Upadhyay MP et al, 1991), Lavaju P et al (Lavaju P et al, 2009) 75% in Nepal and Samar K Basak et al (Basak SK et al, 2005) 57.6%; but a marked contrast was found in a study done in Ghana (Hagan M et al, 1995)where only 16.1% were involved in agricultural activity.…”
Section: Rai Et Al Direct Microscopy In Suppurative Keratitiscontrasting
confidence: 42%
“…Similarly, in a study conducted by U. Gopinathan et al it was seen that the mean age of patients with bacterial keratitis was 41.20 ± 20.36 years and that of patients with fungal keratitis was 30.90 ± 15.28 years, indicating a relatively increased occurrence of corneal infections in the middle age group (Gopinathan U et al, 2009) . In another study conducted by Lavaju P et al, it was seen that ulcers were more prevalent in the middle age groups, between 21-40 years of age (50%) (Lavaju P et al, 2009). Presentation in this age was more common due to the fact that persons belonging to this age group are more active and involve themselves in outdoor activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of patients with infectious keratitis in Eastern Nepal found that 80% were engaged in agricultural work and 68% recalled associated ocular trauma. [3] In addition, 11% had corneal perforation and 9% had endophthalmitis at the time of presentation, suggesting significant delays between the injury and medical evaluation. [3] Poor utilization of eye health services in Nepal has been attributed to limited education (particularly about eye disease) and significant distances between home and health facilities.…”
Section: Introductionmentioning
confidence: 99%